2009
DOI: 10.2147/ijnrd.s4191
|View full text |Cite
|
Sign up to set email alerts
|

The use of everolimus in renal-transplant patients

Abstract: Despite advances in immunosuppressive therapy, long-term renal-transplantation outcomes have not significantly improved over the last decade. The nephrotoxicity of calcineurin inhibitors (CNIs) is an important cause of chronic allograft nephropathy (CAN), the major driver of long-term graft loss. Everolimus is a proliferation signal inhibitor with a mechanism of action that is distinct from CNIs. The efficacy and tolerability of everolimus in renal-transplant recipients have been established in a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
(86 reference statements)
0
10
0
1
Order By: Relevance
“…However, biopsy-proven acute rejection occurred more frequently with everolimus 1.5 mg/day in study A2306 (25%) than in study A2307 (13.7%), suggesting that anti-IL-2 receptor induction therapy is probably beneficial for reducing the risk of early biopsy-proven acute rejection when used with a lower dose of everolimus. 32 The strength of these studies was the documentation that concentration-controlled everolimus in combination with low-exposure cyclosporine results in effective protection against rejection with good renal function (Figure 8). Later on, two further studies compared a high-dose everolimus therapy, very low-dose cyclosporine, and steroid combination with an enteric-coated mycophenolic acid, standard-dose cyclosporine, and steroid combination.…”
Section: 29mentioning
confidence: 99%
“…However, biopsy-proven acute rejection occurred more frequently with everolimus 1.5 mg/day in study A2306 (25%) than in study A2307 (13.7%), suggesting that anti-IL-2 receptor induction therapy is probably beneficial for reducing the risk of early biopsy-proven acute rejection when used with a lower dose of everolimus. 32 The strength of these studies was the documentation that concentration-controlled everolimus in combination with low-exposure cyclosporine results in effective protection against rejection with good renal function (Figure 8). Later on, two further studies compared a high-dose everolimus therapy, very low-dose cyclosporine, and steroid combination with an enteric-coated mycophenolic acid, standard-dose cyclosporine, and steroid combination.…”
Section: 29mentioning
confidence: 99%
“…The lymphocyte incidence is reportedly increased if EVL use begins immediately after renal transplantation. Because EVL produces its effect by arresting the cell cycle, it is frequently used in place of a metabolic inhibitor [5,8]. In 2011, Budde et al reported that they reduced the CNI dose to diminish CNI nephrotoxicity in renal transplantation cases and switched to EVL -based immunosuppressive therapy, which proved effective [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with its possible antineoplastic and antiviral properties, along with cardiovascular protection properties, it aims at improving overall patient survival. 26 In an attempt to maintain a sufficient triple immunosuppressive regimen, EVE was introduced to replace MPA, as MPA was considered responsible for resistant neutropenia. Patients in our study were relative young (range, 15-58 y), 5 of them had received 1 or 2 kidney transplants in the past and had an increased cytotoxic antibody titers, while 70% of the donors were donors with expanded criteria.…”
Section: Discussionmentioning
confidence: 99%